Analisis Pengaruh Disiplin Kerja Dan Motivasi Kerja Karayawan CV. Adeeva Kontruksi Jambi - Indria Mayesti; Abd Halim; Rika Neldawaty; Des Arianti Syarah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The purpose of this research is to explain the analysis of the influence of work discipline and work motivation of Jambi employees (CV. Adeeva Construction Study) simultaneously and partially this type of research used in this research is associative research which aims to determine the relationship between two or more variables. The variables referred to in this study are variable X1 (Work Motivation), variable X2 (Work Discipline) and Y (Performance). The results of the study based on the results of multiple linear regressions proved that the variables of Performance, Discipline, and Motivation had a significant effect on Employee Performance (CV. Adeeva Construction Study). Based on the research results that are expected to be input, PT Adeeva should make performance performance a major part of the company so that the company's activities can run even better. And the need for motivation to all employees to work better in the future by giving rewards to employees who excel in order to motivate all employees to work better.